High-Intensity Exercise Training Protects the Brain Against Autoimmune Neuroinflammation: Regulation of Microglial Redox and Pro-inflammatory Functions - Yifat Zaychik; Nina Fainstein; Olga Touloumi; Yehuda Goldberg; Liel Hamdi; Shir Segal; Hanan Nabat; Sofia Zoidou; Nikolaos Grigoriadis; Abram Katz; Tamir Ben-Hur; Ofira Einstein (Frontiers in Cellular Neuroscience, 2021)
Background: Exercise training induces beneficial effects on neurodegenerative diseases, and specifically on multiple sclerosis (MS) and it’s model experimental autoimmune encephalomyelitis (EAE). However, it is unclear whether exercise training exerts direct protective effects on the central nervous system (CNS), nor are the mechanisms of neuroprotection fully understood. In this study, we investigated the direct neuroprotective effects of high-intensity continuous training (HICT) against the development of autoimmune neuroinflammation and the role of resident microglia.Methods: We used the transfer EAE model to examine the direct effects of training on the CNS. Healthy mice performed HICT by treadmill running, followed by injection of encephalitogenic proteolipid (PLP)-reactive T-cells to induce EAE. EAE severity was assessed clinically and pathologically. Brain microglia from sedentary (SED) and HICT healthy mice, as well as 5-days post EAE induction (before the onset of disease), were analyzed ex vivo for reactive oxygen species (ROS) and nitric oxide (NO) formation, mRNA expression of M1/M2 markers and neurotrophic factors, and secretion of cytokines and chemokines.Results: Transfer of encephalitogenic T-cells into HICT mice resulted in milder EAE, compared to sedentary mice, as indicated by reduced clinical severity, attenuated T-cell, and neurotoxic macrophage/microglial infiltration, and reduced loss of myelin and axons. In healthy mice, HICT reduced the number of resident microglia without affecting their profile. Isolated microglia from HICT mice after transfer of encephalitogenic T-cells exhibited reduced ROS formation and released less IL-6 and monocyte chemoattractant protein (MCP) in response to PLP-stimulation.Conclusions: These findings point to the critical role of training intensity in neuroprotection. HICT protects the CNS against autoimmune neuroinflammation by reducing microglial-derived ROS formation, neurotoxicity, and pro-inflammatory responses involved in the propagation of autoimmune neuroinflammation.